On 4D capabilities of chemical assisted mechanical blended ABS-nano graphene composite matrix. (2022) - Kumar, Vinay; Singh, Rupinder; Ahuja, I.P.S.
Abstract: In past one decade thermoplastic composite matrix reinforced with graphene (Gr) (such as acrylonitrile butadiene styrene (ABS)-Gr, polyamide (PA)-Gr etc.) has been widely explored for 3D printing applications. But hitherto little has been reported on 4D capabilities of ABS-Gr (nano-particles) composite matrix prepared by chemical assisted mechanical blending. In this work, chemical assisted mechanical blending of ABS-Gr has been explored for 4D printing applications by considering magnetic field as stimulus with two way programming feature. The ABS-Gr composite was prepared with different weight proportions (10%, 15% and 20%) with chemical assisted mechanical blending. The twin screw extrusion (TSE) of composite lumps was carried to prepare 3D printing feedstock filament wires. Scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) was performed for morphological analysis of ABS-Gr composites. For 4D capabilities, composites of ABS and Gr were investigated for magnetic properties by performing vibration scanning magnetometry (VSM) test. Fourier transformed infrared spectroscopy (FTIR) of all proportions/compositions was performed to study bond strength analysis of ABS-Gr composite. Morphological analysis based on SEM/EDS has shown increase in carbon content as Gr content was increased. The VSM results showed that composite possesses magnetic properties and can be used for self assembly applications. Composite with composition/proportion ABS + 20%Gr has better magnetization, retentivity and coercivity. FTIR showed increase in bond strength of ABS-Gr composite due to uniform blending of nanoparticles. Further lower absorbance percentage outlined that the prepared composite matrix may be used for sensing low frequency signals in typical remote sensing applications.